"خدا کی بستی" اور" نیلی بار" میں" کارنیوال" کی صورت حال کا تقابلی جائزہ: A Comparative Analysis of Condition of "Carnival" in “Khudā Kiī Bastī” and “Nīlī Bār” (Al-Qamar, 2023)
Mikhail Bakhtin is one of the most influential literary critics of 20th century. He was the Russian Formalist. Bakhtin’s idea of dialogue an authority is rooted in the Medieval. Carnivals were unusual events which were completely against the daily life. In these events, there was a confusion of status. The power classes of the society were ignored in these carnivals. Bakhtin lists the stylistic features into which the “unity” of the novel is usually divided, direct authorial narration, stylization of everyday speech, stylization of semi-literary discourse such as letters and diaries, various types of speech such as moral philosophical scientific statements and the individualized speech of characters.
Keywords: Carnivals; “Khudā Kī Bastī”; “Nīلī Bār”; Comparative